dbGVOSCC: a comprehensive database of genetic variation for systems genetics research on oral squamous cell carcinoma - Zhou, Yi; Wu, Yutao; Shi, Wenjing; Zhang, Yingbo; Liu, Xingyun; Zhang, Yuxin; Zhan, Chaoying; Chen, Bingyue; Tian, Weidong; Shen, Bairong (Frontiers in Oncology, 2025)
IntroductionOral squamous cell carcinoma (OSCC) is a highly aggressive malignancy of the oral epithelium, marked by a high rate of lymph node metastasis and a profound negative impact on patients’ quality of life. Despite its severity, no routine screening program currently exists for OSCC. To address the genetic heterogeneity underlying OSCC, we have developed a database of genetic variation in oral squamous cell carcinoma (dbGVOSCC; http://www.sysbio.org.cn/dbGVOSCC/).MethodsOSCC literature (1991–2024) was queried from PubMed and screened manually and via PubTator, following predefined inclusion/exclusion criteria. Entities and relations were extracted from qualifying articles and organized into tables. The database adopted a browser/server architecture using HTML and XAMPP. Front-end was built with HTML and CSS for web display; server-side used Apache for infrastructure, MySQL for data management, and PHP/JavaScript for backend-frontend integration. Bioinformatics included mapping genes to STRING (confidence >0.9), hub gene identification via PPI degree centrality, and GO/KEGG enrichment with clusterProfiler (FDR-corrected). Usability was assessed using SUS and NPS surveys.ResultsdbGVOSCC comprises 1,788 somatic genetic variation entries from 400 original studies and 106,079 clinical samples, covering epimutations/methylations (329), SNPs (411), point mutations excluding SNP (258), indels (98), CNVs (348), LOH (28), one locus mutation, plus 333 unspecified mutations. We curated 817 biomarker-linked variations (diagnostic n=71, therapeutic n=175, prognostic n=291; 277 multi-application). PPI analysis highlighted 15 key genes (e.g., TP53, CTNNB1, AKT1, EGFR, PIK3CA). Enrichment implicated proliferation, adhesion/migration, p53/DNA damage response, and PI3K–Akt signaling. User testing showed SUS 88.75 (grade A) and NPS 90.DiscussiondbGVOSCC represents a robust and reliable knowledge base, offering clinicians and researchers an open-source platform for personalized genotype-phenotype association studies and systems genetics research into the mechanisms of OSCC.